Pedagogic basics of fundamentalization of prospective economists’ training - Ткач, Юлія Миколаївна (Pedagogy of Higher and Secondary Education, 2017)
The article deals with the pedagogical foundations of prospective economists training fundamentalization. It is noted that the educational point of view on the foundation of vocational training should be considered primarily as a didactic principle. The paper points out the essence of the didactic principle and presents the list that describes the gist of the principle of knowledge fundamentalization. In terms of vocational education fundamentalization each of the didactic system components of prospective economists’ training is highlighted